2008
DOI: 10.1177/154405910808700516
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Amelogenin-MMP20 Interactions in Amelogenesis Imperfecta

Abstract: Amelogenin with a proline 41 to threonine mutation (P41T) is hydrolyzed at a lower rate by matrix metalloproteinase 20 (MMP20), resulting in an inherited tooth enamel defect, amelogenesis imperfecta (AI). The aim of this study was to elucidate the effect of P41T on the interactions between amelogenin and MMP20, which may contribute to the formation of this type of AI. The interactions of a recombinant wild-type human amelogenin and its P41T mutant with recombinant human MMP20 were compared by substrate competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…The T21I mutation destabilizes the disordered structure, and in turn, the relative population of partially folded soluble oligomers is increased. On the other hand, the P41T mutation destabilizes the disordered structure by populating a heterogeneous distribution of small aggregates, which may be the molecular basis for reduced proteolytic processing by MMP-20 (28).…”
Section: Discussionmentioning
confidence: 99%
“…The T21I mutation destabilizes the disordered structure, and in turn, the relative population of partially folded soluble oligomers is increased. On the other hand, the P41T mutation destabilizes the disordered structure by populating a heterogeneous distribution of small aggregates, which may be the molecular basis for reduced proteolytic processing by MMP-20 (28).…”
Section: Discussionmentioning
confidence: 99%
“…The same order applies for the P41T mutant. Recent work on 'amelogenin-to-MMP20' interactions [Tanimoto et al, 2008] also used SPR to calculate relative binding constants. Amelogenin solutions were passed over an immo-bilized layer of deactivated MMP20 and it was found that P41T amelogenin exhibited a lower k (on) signal than did the wild-type rH174 (recombinant human amelogenin).…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian menunjukkan bahwa ekspresi amelogenin kelompok kontrol (K-1) paling rendah dibanding kelompok yang dipajan fluorida yang mempunyai nilai ekspresi paling tinggi. Hal ini disebabkan pada saat proses amelogenesis secara normal, amelogenin akan terdegradasi menjadi beberapa fragmen melalui proses hidrolisis oleh aktivitas Matrixmetalloproteinase-20 (MMP-20) [16][17][18] yang merupakan mediator dari remodeling Gambar 3. A) Gambaran densitas matriks enamel pada kelompok control; B) Gambaran densitas matriks enamel kelompok yang dipajan NaF; C) Gambaran densitas matriks enamel kelompok yang dipajan NaF+NaCl 2 (Pengamatan menggunakan SEM dengan pembesaran 20.000x).…”
Section: Pembahasanunclassified